Quantum field theory : Feynman path integrals and diagrammatic techniques in condensed matter - Fai, Lukong Cornelius (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
"This book explores quantum field theory using the Feynman functional and diagrammatic techniques as foundations to apply Quantum Field Theory to a broad range of topics in physics. This book will be of interest not only to condensed matter physicists but physicists in a range of disciplines as the techniques explored apply to high-energy as well as soft matter physics"--
Symmetry requirements in quantum field theory -- Coherent states -- Non-interacting particles -- Perturbation theory and Feynman diagrams -- (Anti) symmetrized vertices -- The random phase approximation (RPA): screened interactions and plasmos -- Theory of phase transitions and critical phenomena -- Weakly interacting Bose gas -- Path integral formalism for non-ideal Bose gas -- Superconductivity theory -- Path integral approach to the BCS theory: spin-imbalanced Fermi gas -- Green's functions averages over impurities -- Classical and quantum theory of magnetism -- Spin dynamics. dynamical response function -- Itinerant ferromagnetism -- Nonequilibrium quantum field theory.
OCLC-licensed vendor bibliographic record.
Keywords: Quantum field theory; Feynman integrals; Feynman diagrams; Condensed matter; SCIENCE / Energy; SCIENCE / Physics / General